Hymenoptera Parasitoid dan Persentase Parasitasi terhadap Berbagai Ulat Pemakan Daun Kelapa Sawit di Kebun Cikasungka PTPN VIII, Cindali, Bogor - Ichsan Luqmana Indra Putra; Pudjianto Pudjianto; Nina Maryana (Fakultas Biologi | Universitas Jenderal Soedirman, 2021)
Palm oil is one of the plantation commodities in Indonesia and had widespread in Indonesia. One of pests that attack oil palm is insect, and the most damaging pests usually from Lepidoptera. The aim of this study was to determine and counting percent parasitization of the parasitoids that parasitize palm leaf-eating pests in the oil palm plantation of PTPN VIII Cindali, Bogor. The study was conducted in 6 blocks of PTPN VIII Cindali oil palm plantation from September 2014 - June 2015 with observations once a month. Sample was taken by means of each block taken 5 plants in every plots randomly to be observed and palm leaf-eating insects taken to kept until the parasitoid was emerged. The outgoing parasitoids then counted and identificated. The results of the study founds 6 species of palm leaf-eating pests and 5 species of Hymenoptera parasitoids that parasitize these pests. Pests that found were Setora nitens, Amatissa sp., Birthosea bisura, Mahasena corbetti, Metisa plana and Pseudococcus sp. Whereas parasitoids that found were Spinaria spinator, Charops bicolor, Telenomus podisi, Aphanogmus sp. and Acerophagus sp.